2020
DOI: 10.17113/ftb.58.01.20.6239
|View full text |Cite
|
Sign up to set email alerts
|

Application of Spectrophotometric Fingerprint in Cluster Analysis for Starch Origin Determination

Abstract: The botanical origin of starch is of importance in industrial applications and food processing because it may influence the properties of the final product. Current microscopic methods are time-consuming. Starch consists of an origin-dependent amylose/amylopectin ratio. Triiodide ions bind characteristically to the amylose and amylopectin depending on the botanical origin of the starch. The absorbance of the starch-triiodide complex was measured for wheat, potato, corn, rye, barley, rice, tapioca and unknown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In Figure S1b, the spectra show three different peaks in the UV–vis region. The first two peaks are assigned to triiodide/iodide ions, while the peak with the largest absorption at 560 nm is considered to be an amylopectin–triiodide complex, and the intensity of GCS is higher than that of CS, which is consistent with the GPC results. This may promote the disorder degree of HC samples during subsequent precarbonization and carbonization processes.…”
Section: Resultssupporting
confidence: 84%
“…In Figure S1b, the spectra show three different peaks in the UV–vis region. The first two peaks are assigned to triiodide/iodide ions, while the peak with the largest absorption at 560 nm is considered to be an amylopectin–triiodide complex, and the intensity of GCS is higher than that of CS, which is consistent with the GPC results. This may promote the disorder degree of HC samples during subsequent precarbonization and carbonization processes.…”
Section: Resultssupporting
confidence: 84%
“…One of the most popular natural polysaccharides used in snack manufacture is starch, being a carbohydrate made of amylose and amylopectin fractions. Its botanical origin determines the main changes in starch processing and quality of final products [Sakač et al, 2020]. Starches of various biological origin differ in the degree of polymerization, the amylose to amylopectin ratio, and molecular organization of the crystalline regions of granules [Błaszczak et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Whole wheat flour contained 0.50 g and refined wheat flour contained 0.65 g of resistant starch, respectively, ( 40 ). Retrogradation of resistant starch rate depends on starch properties like its type of structure, cooking and storage duration, time and temperature ( 11 ). In the current investigation, we found that dalia followed by parantha , chapatti and poori, stored at 4°C for 24 h (T3) followed by stored at room temperature (T2) had higher RS content than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Starch structures that are molecular or crystalline are affected by storage conditions like duration, temperature and water content, which determine the retrogradation rate and its extent. Wheat starches show higher retrogradation rates due to longer amylopectin chains and high amylose (21.7%) content compared to rice (17.55%) ( 11 ). A high amylose content leads to low digestibility in food products ( 12 ).…”
Section: Introductionmentioning
confidence: 99%